Key elements for designing effective second victim support interventions: a focus group study in European clinical settings - José Joaquín Mira; Irene Carrillo; Kris Vanhaecht; Deborah Seys; Massimiliano Panella; Susanna Tella; Katja Schrøder; Reinhard Strametz; Paulo Sousa; Bojana Knezevic; Kaja Pölluste; Eva Gil-Hernández; et al. (BMJ Open)
Background The second victim (SV) experience limits the performance of health and care workers and places patients at risk. Peer support is recognised as the most effective, feasible and acceptable intervention to mitigate its impact.Objective To define a set of success factors when designing interventions to support SVs in health and care facilities based on expertise in different European countries.Setting International collaboration involving countries with diverse cultures, structures and legal frameworks.Design Qualitative research.Method Focus groups involving a total of 43 participants were conducted in five countries. Prominent professionals in European peer support interventions were engaged. Analysis of common elements considered key to the success of these programmes was underscored.Results Critical success factors for designing effective SV support interventions included the need for an occupational health approach, the establishment of a strong organisational safety culture, immediate psychological first aid, long-term resilience building, the engagement and training of peer supporters, the provision of adequate resources and ongoing support, the importance of leadership commitment and the necessity of tailoring interventions to the specific context and needs of each institution and country considering their diverse sociocultural and legal framework. The expected benefits included ensuring optimal patient care and reducing associated costs such as staff turnover and litigation.Conclusion Effective SV support interventions are essential for enhancing the resilience and performance of health and care workers, ultimately improving patient safety. By implementing tailored and well-resourced interventions, healthcare institutions can mitigate the negative impact of the SV phenomenon, promoting optimal care.